Vehicle Traffic Estimation Using Deep Learning - Meetkumar Patel; Daniel Silver (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
For commuters, vehicular traffic is an important planning concern. People have access to the weather forecast and the current traffic situation, but there is no application available to estimate traffic congestion and flow in the near future. Thus, we design and develop a machine learning approach which can predict vehicular traffic density and flowrate up to two days in the future based on the weather, calendar and special events data.